A brief overview of literary Darwinism and a Darwinian perspective on The Road by Cormac McCarthy - Malina Załużna-Łuczkiewicz (Language, Culture, Politics)
The first section of this paper presents in general terms the main ideas of literary Darwinism represented by Joseph Carroll, Jonathan Gottschall and other scholars concerning theory (literature as an adaptation) and interpretative practice. It also reviews the key arguments of this literary school's critics focusing on the papers of Jonathan Kramnick and William Deresiewicz. The second section is an attempt at applying Darwinian methodology to the interpretation of The Road by Cormac McCarthy taking into account its reception, style, the behavioural systems (survival, parenting, and cognitive activity), the literary context and the author's point of view.